UTILIZATION OF ORGANIC MATERIALS TO IMPROVE CELERY (Apium graveolens L.) YIELD - Kornelis, Veri; Widowati; Sutoyo (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Celery (Apium graveolens L.) is a leaf vegetable and medicinal plant usually used as a cooking spice. Several countries, including Japan, China, and Korea, use the leaf stalks as a food ingredient. The demand for celery continues to increase yearly, both domestically and abroad. Celery cultivation is rarely done in big cities because environmental conditions are unsuitable for growth requirements. Fertilization technology is one of the determinants in efforts to improve the quality and quantity of agricultural products. The use of appropriate fertilizer is expected to achieve economically profitable production levels. Fertilization essentially provides nutrients into the soil so plants' nutrient needs can be met. This research aims to determine the best use of organic fertilizer in increasing the growth and yield of celery plants. This research was conducted from June to September 2024 and is located in Tirto Rahayu, Rambaan Hamlet, Dau District, Malang Regency, East Java. This research used a Randomized Block Design with 7 treatments and 4 replications consisting of A1 (22 grams of urea), A2 (2.5 grams of humus), A3 (200 grams of goat manure), A4 (200 grams of chicken manure mixed with husks), A5 (2.5 grams of humus + 22 grams of urea), A6 (200 grams of goat manure + 22 grams of urea), and A7 (200 grams of chicken manure + 22 grams of urea). The research showed that A3 (200 grams of goat manure per plant) gave the best results, affecting plant height, number of leaves, wet weight, and volume of celery.